Władysław Orkan’s Peasant Narrations, Or On the Benefits of History of Literature for the Folk Turn - Kuc, Marcelina (Literatura Ludowa. Journal of Folklore and Popular Culture, 2026)
The aim of the article is to examine Władysław Orkan’s oeuvre from the perspective of the contemporary folk turn. Having debuted in 1897, the writer can be seen as a precursor of the peasant trend in Polish prose. Analyses of his novels Komornicy, W Roztokach and Kostka Napierski, as well as his journalistic cycle Listy ze wsi lead in a reflection on the way the writer strove to create a new peasant-based paradigm in literature, as an alternative to the culture of nobility and intelligentsia. These considerations culminate in addressing the extent to which the current folk turn continues the tradition of Orkan’s peasant narratives.